Mining claim No. 1 at Dry Creek, Alaska, approximately 1901. - Hegg, Eric A., 1867-1948 (1901)
Probably Dry Creek that flows into the Snake River at Nome. Shows five men and a woman with gold pan, pickaxes and rocker. Caption on image: "No. 1 Dry Creek" Original image in Hegg Album 28, page 24. Original photograph by Eric A. Hegg 1808; copied by Webster and Stevens 285.A Nome Gold Rush.